Promoting sustainable practices in the semiconductor industry through cull and runner recycling - Liu, Yuqi (Nanyang Technological University, 2025)
While a cornerstone of modern technology, the semiconductor industry generates substantial waste during the package production. This could pose environmental and waste management challenges. As the world shifts toward a more sustainable future, recycling has become increasingly important. This study focuses on the recycle of unwanted culls and runners, which essentially are semi-cured epoxy molding compounds (EMC), generated during the molding process. The literature review provides deeper understanding on the recycling methods and challenges faced by the semiconductor industry. We also explore the mechanical griding of culls and runners, followed by material characterization using the scanning electron microscopy (SEM), thermogravimetric analysis (TGA), and differential scanning calorimetry (DSC) techniques, etc.. An established method and proper material characterization will pave the way for the upcycling of waste into high value applications.